G‘AFUR G‘ULOM AND FOLKORAL CREATIVITY (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the poet's important information about boasters and jokers, as well as his mastery in using proverbs, various phraseological expressions, praises, and curses in his poetry.